Swimming, back pain and electromyography: A brief review - D'Anna, C.; D'alessandro, A.; Vastola, R. (Journal of Human Sport & Exercise, 2020)
Background: The low back is the most common site of pain in the population, especially in the adolescent population. Several scientific studies in the literature focused on swimming, its effects and the relationship with injuries and deformities of the spine. Purpose: this brief review, in an attempt to answer this question, aims to compare several studies that have focused attention on the relationship between the possible appearance of postural problems and swimming activity practiced at a competitive level. Methods: a literature search was conducted for articles published between 2000 and 2020 with the exception of two pilot studies from the 1990s.The review was carried out in the following databases: Web of Science, PubMed, Scopus, Science Direct and Google Scholar. In addition, further studies were consulted by accessing specific journals. The search terms used were: swimming, electromyography, back-pain, muscles activity, scoliosis, and crawl. To select the studies, the following criteria were identified: use of electromyography as an investigation tool; sample of competitive swimmers aged between 12 and 17 years. Results: the results were summarized in a table indicating authors, year of publication, objective, sample, swimming style analysed, research methodology and specific results. The analysis of the literature generally shows the existence of a relationship between intensity of training and the occurrence and aggravation of dysmorphisms or paramorphisms. In addition, the selected studies show the importance assigned to core training in the prevention of postural imbalances.